Understanding Cultural Drivers of E-Wallet Continuance Intention among Micro and Small Enterprises in Indonesia - Anna Widayani; Nilawati Fiernaningsih; Pudji Herijanto; Rani Arifah Normawati; Dwi Herlindawati (goodwood publishing, 2026)
Purpose: This study aims to explore the factors influencing e-wallet usage intention among Micro and Small Enterprises (MSE) owners in Indonesia by combining the Technology Acceptance Model (TAM) with cultural aspects. Research Methodology: This study used a quantitative survey of 170 micro and small business owners in Indonesia. Data were gathered through a structured questionnaire and examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) with statistical analysis software. Results: The findings revealed that perceived ease of use and uncertainty avoidance significantly influenced the continuance intention to use e-wallets. Perceived usefulness does not directly affect continuance intention, while collectivism significantly influences perceived usefulness but does not directly impact continued usage. Conclusions: The results suggest that MSE owners’ long-term adoption of e-wallets is strongly driven by system usability and their perception of risk and uncertainty. Cultural context also shapes users’ evaluation of digital financial technologies. Limitations: This study focuses on MSE owners in Indonesia with a small sample size and cross-sectional design, which may limit how widely the findings can be applied. Contributions: This study adds to the existing knowledge on fintech adoption by enhancing the Technology Acceptance Model with cultural aspects in the context of developing nations. The results also offer useful information for fintech firms and government officials to create user-friendly and reliable digital payment solutions.